Symptom Overlap and Screening for Symptoms of Attention-Deficit/Hyperactivity Disorder and Psychosis Risk in Help-Seeking Psychiatric Patients - Corbisiero, Salvatore; Riecher-Rössler, Anita; Buchli-Kammermann, Jacqueline; Stieglitz, Rolf-Dieter (Frontiers in Psychiatry, 2017)
Symptoms of attention-deficit/hyperactivity disorder (ADHD) and psychosis risk share features which might represent an early vulnerability marker for schizophrenia. Early detection of individuals with this symptomatic overlap is relevant and may assist clinicians in their decision making for diagnosis and treatment. This study sought to analyze the capability of different instruments in the screening of patients for ADHD symptoms or at psychosis risk, assess their classification accuracy and describe the extent of symptoms overlap between them. 243 adult patients completed one instrument screening for ADHD and two instruments screening for psychosis risk symptoms (Adult ADHD Self-Report Scale Symptom Checklist (ASRS-v1.1); Prodromal Questionnaire Brief Version (PQ-16); Self-Screen Prodrome (SPro)). The ability of these instruments to distinguish between the symptomaticity of these patients appears modest. The most satisfactory scale to identify subjects at psychosis risk was SPro with its subscale psychosis risk. ASRS-v1.1 showed good reliability in assessing individuals as not having ADHD symptoms and had higher probability to achieve its own and the cut-off of another questionnaire. Subjects having symptoms of psychosis risk and ADHD showed elevated symptomatology. Reliable instruments capable of separating ADHD symptoms from those of psychosis risk are needed to better identify the symptomatic overlap of this two conditions.